GAMBARAN INDEKS MASSA TUBUH PADA PASIEN KANKER YANG MENJALANI KEMOTERAPI - Hardiano, Randi '; Huda, Nurul '; ', Jumaini ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Cancer is an abnormal growth of cells which tend to invade surrounding tissue and spread to organs of the body. One treatment in cancer patients is to use chemotherapy. The side effects of chemotherapy are diverse, including nausea vomiting, anorexia which led to weight loss. The purpose of this research was to know body mass index in cancer patients undergoing chemotherapy. The methods used in this research was descriptive. This research was conducted at the RSUD Arifin Achmad Pekanbaru involving 51 respondents with sampling method was purposive sampling. Univariate analysis was used. The research results obtained here the respondents on IMT status normal was 25 respondents (49%), fat obese I8 respondents (15.7%), skinny light level as much as 7 respondents (13.7), skinny weight levels as much as 6 respondents (11.8), obese II obese 4 respondents (7.8), fat level lightweight as much as 1 respondents (2%). The results of this research are expected to give an overview to the medical personnel associated with the status of the IMT in cancer patients undergoing chemotherapy, so that it can monitor and minimize the disruption to the nutrition in patients undergoing chemotherapy. Keywords: BMI, cancer, chemotherapy.